HATHA YOGA TRAINING HAS SIMILAR EFFECTS WITH TAI CHI TRAINING IN DECREASING BLOOD PRESSURE IN PRE-ELDERLY WITH GRADE I HYPERTENSION - Elisabeth Matrona Sintia Pareira; I Dewa Putu Sutjana; Wahyuddin Wahyuddin; Nyoman Adiputra; I Made Krisna Dinata; I Gusti Ayu Widianti (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
The increase of life expectancy theis more complex health problem is which suffered by the elderly. The problem in health which is often occurred that is instability of blood pressure which dominated by hypertension. One of methods to decrease high blood pressure is by increasing physical activity. Physical activity reduces the risk of hypertention by decreasing resistance of blood pressure and surpressing the activity in sympathetic nerves system and renin-angiotensin system. This research aims to discover Hatha Yoga training and Tai Chi traning in decreasing blood pressure in pre-elderly with grade I hypertension in Banjar Batu, Mengwi sub-distict, Badung Regency. This research used experimental design with pre test and post test two group design. Group I was given Hatha Yoga and Group II was given Tai Chi. The sample in this research is 20 people (man and woman) who suffered grade I hypertension and aged in 45-49 years old. The training was done in 3 times a week for 6 weeks. The result of the research shows that the decrease of blood pressure is shown Group I in systole is 5,60±1,43 mmHg and diastole is 4,00±1,94 mmHg, with value p=0,00. In Group II, there is a decrease in systole blood pressure is 4,90±0,99 mmHg and diastole 4,30±2,05 mmHg, with value p=0,00. There is no significant difference in the decrease of blood pressure between Group I and Group II with blood pressure in systole is p=0,378 (p>0,05) and in diastole is p=0,805 (p>0,05). The conclusion is that Hatha Yoga training is as goof as Tai Chi training in decreasing blood pressure in pre-elderly with mild hypertention. Keywords: Hatha Yoga; Tai Chi; Pre Elderly; Grade I Hypertension